Research handbook on European State aid law - Szyszczak, Erika M. (Cheltenham, U.K. : Edward Elgar, 2011)
'This timely new Handbook reflects on current issues that confront State aid law and policy in the EU. State aid was a neglected area of competition law until attempts to modernize it became central to the Lisbon process 2000 where the aim was to encourage'intelligent' State aid by reducing aid to specific sectors and by making better use of aid for horizontal projects central to EU integration concerns. This policy framework has underpinned the new approach to State aid policy in the EU in recent years and informs many of the chapters in this book. Contributions from leading academics, regulators and practising lawyers, discuss topics devoted to modernization, problems faced by recent enlargements of the EU, the role of State aid in the fiscal crisis and recession, the role of the private market investor test, regional aid, environmental aid and the review of the Altmark ruling. Perspectives on State aid law and policy from the disciplines of economics and political science are also explored in detail'--Provided by publisher.
Modernization of State aid policy / Thibaut Kleiner -- State aid control from a political science perspective / Michael Blauberger -- State aid in the accession states / Alexander Birnstiel and Helge Heinrich -- The role of economics in State aid analysis and the balancing test / Lorenzo Coppi -- The market economy investor : an economic role model for assessing State aid / James Kavanagh, Gunnar Niels and Simon Pilsbury -- The intersection between the market economy investor principle and the one time-last time principle in the context of airline restructuring operations / Antigoni Lykotrafiti -- The Great Recession and other mishaps : the Commission's policy of restructuring aid in times of a crisis / Christian Ahlborn and Daniel Piccinin -- The concept of selectivity? / Andreas Bartosch -- State aid and taxation in EU law / Claire Micheau -- Regional State aid / Maja-Alexandra Dittel and Klaus-Otto Junginger-Dittel -- State aid in the energy sector / Leigh Hancher and Francesco Salerno -- The relationship between State aid and the single market / Andrea Biondi and Martin Farley -- Altmark assessed / Erika Szyszczak -- European economic rights and national State aid policy in conflict : the problem of the democratic securing of welfare / Michelle Everson -- Procedural aspects of EU State aid law and practice / Michael Schutte -- Judicial review of Commission decisions in State aid / Herwig C.H. Hofmann and Alessandro Morini -- State aid and the role of national courts / Paolisa Nebbia -- State aid (subsidies) in international trade law / Rike Kramer and Markus Krajewski.
Includes bibliographical references and index.
Keywords: Subsidies -- Law and legislation -- European Union countries; Government aid -- European Union countries; Government aid -- Law and legislation -- European Union countries